Performances of the Synergy of Silica Fume and Waste Glass Powder in Ternary Blended Concrete - Moruf Olalekan Yusuf; Khaled A. Alawi Al-Sodani; Ali H. AlAteah; Mohammed M. H. Al-Tholaia; Adeshina A. Adewumi; Azeez Oladipupo Bakare; Abdullahi Kilaco Usman; Ibrahim Momohjimoh (Applied Sciences, 2022)
The quest to enhance public health and the need for a reduction in the environmental solid wastes have prompted this study. Despite abundant studies on silica fume (SF or S) and waste glass powder (WGP or G), there is a need to understand the interaction of WGP with SF in the production of ordinary Portland cement (OPC or C)-based concrete using the water/binder ratio of 0.42. The investigated concrete comprised 90 wt.% of OPC and 10 wt.% of WGP+SF. The samples were denoted as C90GxS10−x such that x varied from 0–10 wt.% at the interval of 2.5. The findings revealed that an increase in the WGP/SF ratio enhanced the absorption of silica/glass blended concrete due to size incompatibility and proliferations of interfacial transition zones between the glass particle, silica fume and cement matrix. The density of fresh OPC concrete was higher than that of glass/silica blended concrete due to the difference in their relative densities. Incorporating WGP and SF in synergy enhanced silicate reorganization and led to a more amorphous binder and a reduction in hydroxyl-based compounds such as portlandite but caused microstructural heterogeneity in the morphology of the binder as obtained from XRD, FTIR and SEM/EDS results. The 28-day compressive strength of 46 MPa is achievable if the WGP and SF are kept within 2.5–5 wt.% and 5–7.5 wt.%, respectively. The study will foster the production of economic, environmental, and cost-efficient concrete.